Phylogenetic Relationships and Potential Functional Attributes of the Genus Parapedobacter: A Member of Family Sphingobacteriaceae - Nagar, Shekhar; Talwar, Chandni; Haider, Shazia; Puri, Akshita; Ponnusamy, Kalaiarasan; Gupta, Madhuri; Sood, Utkarsh; Bajaj, Abhay; Lal, Rup; Kumar, Roshan (Frontiers in Microbiology, 2020)
The genus Parapedobacter was established to describe a novel genus within the family Sphingobacteriaceae and derives its name from Pedobacter with which it is shown to be evolutionarily related. Despite this, they do not share very high 16S rRNA gene sequence similarities. Therefore, we hypothesized whether these substantial differences at 16S rRNA gene level depict the true phylogeny or these genomes are actually diverged. Thus, we performed genomic analysis of the four available genomes of Parapedobacter to better understand their phylogenomic position within family Sphingobacteriaceae. Our results demonstrated that Parapedobacter are more closely related to species of Olivibacter as opposed to the genus Pedobacter. Further, we identified a significant class of enzymes called pectinases with potential industrial applications within the genomes of P. luteus DSM 22899T and P. composti DSM 22900T. These enzymes, specifically pectinesterases and pectate lyases are presumed to have largely different catalytic activities based on very low sequence similarities with already known enzymes and thus may be exploited for industrial applications. We also determined complete Bacteroides Aerotolerance (BAT) operon (batA, batB, batC, batD, batE, hypothetical protein, moxR and pa3071) within genome of P. indicus RK1T. This expands the definition of genus Parapedobacter to containing members that are able to tolerate oxygen stress using encoded oxidative stress responsive systems. By conducting a signal propagation network analysis, we determined that BatD, BatE and hypothetical proteins are the major controlling hubs that drive the expression of BAT operon. As a key metabolic difference, we also annotated complete iol operon within P. indicus RK1T genome, for utilization of all three stereo-isomers of inositol namely, myo-inositol, scyllo-inositol and 1D-chiro-inositol which are abundant source of organic phosphate found in soils. The results suggest that genus Parapedobacter hold promising applications owing to their environmentally relevant genomic adaptations which may be exploited in future.